Pengaruh Revitalisasi Dan Penataan Ulang Pedagang Terhadap Perekonomian Pedagang Kota Padang Dalam Menghadapi Pasar Bebas Asean (Studi Kasus: Pasar Raya Kota Padang) - Devi Edriani; Harmelia Harmelia (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2018)
The revitalization of traditional markets is one of the government programs in increasing the local revenue (PAD) in general, and the market economy of Pasar Raya traders in Padang City. The purpose of this study is to determine the effect of traditional market revitalization and rearrangement of traders on the merchant's economy in Pasar Raya Kota Padang in the face of competition of Asean Free Market (MEA). The sample in this study amounted to 257, is part of all traders in traditional markets that have been revitalized in the city of Padang. The data source is primary data and secondary data, the primary data in the form of questionnaires conducted on the respondents and interviews, while the secondary data is data about the number of kiosks and traders before the revitalization and after revitalization as well as data on the rearrangement of the placement of traders after the revitalization obtained from the Trade Service of Padang City. This research uses multiple linear regression analysis method. The results showed Y = 24.481+ 0.591X1 + 0.825X2. Through the result of calculation processed using SPSS obtained t test value and f test that revitalization, trader rearrangement have influence of significance to merchant economy. Keywords: Revitalization, Merchant Reorganization, Merchant's Economy.